USING METHODOLOGICAL COMPETENCE-ORIENTED PROBLEMS IN THE TRAINING OF MATHEMATICS TEACHERS AS A PEDAGOGICAL ISSUE - O‘rinov Khalimjon (Modern American Journals, 2025)
This article is dedicated to the training of modern mathematics teachers. It thoroughly explores the development of their ability to apply the knowledge acquired in higher education to their professional practice, as well as the role of this competence in their professional activities.
Keywords: Competency-based approach, professional activity, educational process, competence, professional competence, competence-oriented problem.